1994
DOI: 10.1007/bf00972145
|View full text |Cite
|
Sign up to set email alerts
|

The intersection of class and age: Mother-in-law/daughter-in-law relations in rural Taiwan

Abstract: This paper compares relations between mothers-in-law and daughters-in-law at two points of time in a Taiwanese village which has changed over the past 30 years from an economic system based almost entirely on agriculture to one founded predominantly on off-farm employment. Using ethnographic data, it describes how women's intergenerational relations in contemporary Taiwan both refute and support the notion that Chinese women, who are unquestionably treated as inferiors in their younger years, usually are obeye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…Other previous research indicates that conflicts between daughters-in-law and their mothers-in-law are more common and more serious than conflicts between daughters and their mothers, especially in rural areas (Meng 2002; Pearson 2002; Zheng and Lin 1994). Additionally, the strengthening of the nuclear family (as opposed to the extended family) and increases in free-choice marriage in recent years may lead to stronger bonds between sons and their wives which increase conflicts between daughters-in-law and mothers-in-law (Gallin 1994). As men are less likely to be hands-on caregivers than women, there is lower potential for conflict between old parents and their sons-in-law.…”
Section: Discussion and Public Health Policy Considerationsmentioning
confidence: 99%
“…Other previous research indicates that conflicts between daughters-in-law and their mothers-in-law are more common and more serious than conflicts between daughters and their mothers, especially in rural areas (Meng 2002; Pearson 2002; Zheng and Lin 1994). Additionally, the strengthening of the nuclear family (as opposed to the extended family) and increases in free-choice marriage in recent years may lead to stronger bonds between sons and their wives which increase conflicts between daughters-in-law and mothers-in-law (Gallin 1994). As men are less likely to be hands-on caregivers than women, there is lower potential for conflict between old parents and their sons-in-law.…”
Section: Discussion and Public Health Policy Considerationsmentioning
confidence: 99%
“…Grandparent/grandchild relationships may vary by culture or ethnic group. For example, researchers have reported that in-law relationships are more tension laden in Asian cultures, stemming from traditions in which daughters-in-law joined their husbands' families (Gallin, 1994). More tension-laden relationships with daughters-in-law might intensify the influence of these ties on negative aspects of relationships with grandchildren.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…Traditionally, Taiwanese women gained status within the family over the life course as they gave birth to a son and, later, as the family head’s wife who directs and controls household resources and labour, particularly those of her daughter-in-law (Gallin 1986; Gallin 1994). However, with economic development and more opportunities for men and women to work outside the family, some members of the younger generation have become less dependent on familial resources for their economic well-being, shifting power and control away from the older generation (Gallin 1994). An older woman’s status in the family, then, may be tied more to the support provided to children and grandchildren (Gallin 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, with economic development and more opportunities for men and women to work outside the family, some members of the younger generation have become less dependent on familial resources for their economic well-being, shifting power and control away from the older generation (Gallin 1994). An older woman’s status in the family, then, may be tied more to the support provided to children and grandchildren (Gallin 1994). Thus, women’s perceptions of their social rank in later-life may improve as their daughters and daughters-in-law have children and grow to rely upon their older mothers for help with raising children and other daily tasks.…”
Section: Discussionmentioning
confidence: 99%